2020
DOI: 10.3390/jmmp4020032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Machining Parameters on Finishing Additively Manufactured Nickel-Based Alloy Inconel 625

Abstract: Metal additive manufacturing processes such as selective laser melting (SLM), laser powder bed fusion (L-PBF), electron beam melting (EBM) and laser metal deposition (LMD) can produce additively manufactured nearly fully dense parts with high geometrical complexity. These are often used as components in automotive, aerospace and medical device industries. Finish machining of these components is required to achieve the desired surface finish and dimensional tolerances. The investigations on additively manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It is known that the processed surface structure has a great influence on the equipment performance of parts such as fatigue life, wear and corrosion strength, and is closely connected to cutting conditions. It was also found that the fine structure of the alloy produced by the laminating process, unlike casting and forging, also affects the surface finish of the laminated geographic feature after the laminating process [95]. As shown in Figure 10, classics related to surface topography (defects and roughness), microstructure changes (deformation, particle miniaturization and texture) and mechanical characteristics (fine hardness and residual stress).…”
Section: Surface Integrity (Yüzey Bütünlüğü)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the processed surface structure has a great influence on the equipment performance of parts such as fatigue life, wear and corrosion strength, and is closely connected to cutting conditions. It was also found that the fine structure of the alloy produced by the laminating process, unlike casting and forging, also affects the surface finish of the laminated geographic feature after the laminating process [95]. As shown in Figure 10, classics related to surface topography (defects and roughness), microstructure changes (deformation, particle miniaturization and texture) and mechanical characteristics (fine hardness and residual stress).…”
Section: Surface Integrity (Yüzey Bütünlüğü)mentioning
confidence: 99%
“…), Nimonic (75, 80A, 90, 263, PE 11, C-263, etc. ), Rene (41,95), Udimet (400, 500, 630, 700, etc. ), Pyromet 860, Astroloy, Waspaloy, Unitemp AF2-IDA6, Cabot 214 and Haynes 230 [25].…”
Section: Nickel-based Superalloys (Nikel Esaslı Süper Alaşımlar)mentioning
confidence: 99%
“…Meanwhile, the relationship between σ and Z can be described by power exponential relation at a high stress level, such as Equation ( 4). In the actual production, the hot deformation of Inconel 625 is under the full stress level, and the relationship between σ and Z is shown in Equation (5).…”
Section: The Establishment and Solution Of Constitutive Modelmentioning
confidence: 99%
“…Due to the stable matrix elements and the large extent of the γ" phase, Inconel 625 has excellent high-temperature strength and structural stability [1][2][3][4]. In addition, Inconel 625 has good machinability and weldability [5,6]. Therefore, Inconel 625 can be easily processed into various components such as plates, bars, pipes, wires, and strips [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ji et al [9] analysed the machinability of Inconel 718 during the micro-milling process. In the research [10] studied the effect of cutting parameters during end milling on Inconel 625 parts manufactured by using the Laser Powder Bed Fusion process. Zhang et al [11] studied the machinability of Ti6Al4V in high-speed dry milling with ceramic flute tools.…”
Section: Introductionmentioning
confidence: 99%